Strategi Pengembangan Program Tahfid Dalam Meningkatkan Minat Masyarakat di Madrasah Diniyah Miftahul Ulum - Sa'diah, Nur Halimatus; Agustin, Maulid (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This study explores the development strategy of tahfidz program in Madrasah Diniyah Miftahul Ulum with the aim of increasing community interest in learning the Quran. Religious education plays a crucial role in shaping the character and morals of individuals, but Madrasah Diniyah faces various challenges, such as the high cost of education and the limited number of teachers. The research method used was qualitative with a case study approach, which involved in-depth interviews and documentation analysis to identify factors that influence community interest. The results showed that parental and community support is very influential in motivating children to learn the Quran. The tahfidz program implemented in this madrasah received a positive response from the community, who saw it as an important step in preparing the younger generation for higher religious education. Although there are challenges, such as the low interest of early childhood and the lack of parental support at home, the addition of teaching staff, the provision of tahsin classes, and solid cooperation between teachers, parents and students are expected to increase community participation. This research is expected to contribute significantly to the development of Quran education at the local level and encourage the sustainability of tahfidz programs in the future.